Aging method, USDA quality grade, and endpoint temperature affect eating quality of beef longissimus lumborum steaks - E. Obuz; V. Gok; L. Akaya; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 2012)
Tenderness is one of the most important factors affecting consumers' perceptions and acceptance of palatability. Tenderness is affected by both myofibrillar proteins and connective tissue content and quality. Both marbling and carcass maturity can have a significant effect on beef palatability, with higher consumer sensory scores generally given to USDA Choice loin steaks than to Select steaks for tenderness, juiciness, and overall palatability. Endpoint temperature can also have a significant effect, with higher endpoint temperatures generally decreasing palatability. Aging beef is a common practice in the meat industry because it increases tenderness and flavor development. The meat industry generally utilizes two types of aging, vacuum and dry aging. Vacuum aging, in which meat is aged in a sealed barrier package at refrigerated temperatures, is the most widely used practice. Dry aging refers to aging meat without packaging, and requires greater environmental control to achieve consistent product quality. Vacuum-aged beef has a sourer and stronger bloody/serumy flavor, whereas dry-aged beef has a more beefy, brown-roasted flavor. Dry aging generally results in greater aged flavor of steaks with no advantage for tenderness, and it is a costly procedure because of decreased yields due to greater weight and trim losses than vacuum aging. Flavor benefits of dry aging and distinct yield advantages of vacuum aging stimulated researchers to develop a "special bag" with a very high water vapor transmission rate and very low oxygen transmission rate to decrease shrink and trim loss but create a dry-aged flavor.
Keywords: Cattlemen& #x27; s Day; 2012; Kansas Agricultural Experiment Station contribution; no. 12-231-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1065; Beef Cattle Research; 2012 is known as Cattlemen& #x27; s Day; Beef; Quality grade; Temperature; Longissimus lumborum; Tenderness